Cleopatra - Wanger, Walter; Mankiewicz, Joseph L.; MacDougall, Ranald; Buchman, Sidney; Taylor, Elizabeth, 1932-; Burton, Richard, 1925-1984; Twentieth Century Fox Home Entertainment, Inc (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2001)
Taylor stars as the ambitious queen of Egypt whose involvement with Marc Anthony and Julius Caesar led to her eventual downfall and suicid
Director of photography, Leon Shamroy; production design, John DeCuir; editor, Dorothy Spencer; music, Alex North
Casts: Elizabeth Taylor, Richard Burton, Rex Harrison, Pamela Brown, George Cole, Hume Cronyn
Keywords: Cleopatra, -- Queen of Egypt, -- d. 30 B.C. -- Drama; Caesar, Julius -- Drama; Antonius, Marcus, -- 83?-30 B.C. -- Drama; Historical films; Feature films; Egypt -- History -- Drama